Meaning and authority: the social construction of an 'author' among information behaviour researchers - Michael Olsson (Information Research: An International Electronic Journal)
Introduction. The study explores the social processes that influence the construction by academic (information behaviour) researchers of the meaning/s and significance/s of an author and her work prominent in the literature of their field (Brenda Dervin). Method. Semi-structured qualitative interviews, based in part on the 'Life-Line' and 'Time-line' techniques developed by Dervin and her collaborators. Participants were purposefully sampled to reflect a range of experience levels and conceptual approaches.. Analysis. The study adopted an inductive approach to data analysis, based on the 'constant comparison' approach of Glaser and Strauss. Feedback from participants was sought throughout the analysis process via email. Results. 'Interactions and Relationships' describes the social contacts involved in their construction of the author; 'The Role of Existing Constructions' deals with participants' existing knowledge and understandings; and 'Accepted and Contested Constructions' demonstrates how they drew on their existing constructions in order to accept or contest the constructions of the author conveyed to them Conclusion. Participants' constructive processes involved drawing on their previous experience ('existing constructions') in order to accept or contest the constructions of the author conveyed to them in each new encounter. Participants' constructive processes had two interdependent aspects: the construction of meaning and the construction of authority.